PENILAIAN KELOMPOK TANI TERHADAP PELAKSANAAN FUNGSI PENYULUH PERTANIAN DI DESA TATENGESAN SATU KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA (Studi Kasus : Kelompok Tani Marapuan Jaya dan Kelompok Tani Pasan Jaya) - Christofel Joshua Ngongoloy; Elsje Pauline Manginsela; Benu Olfie Liesje Suzana (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the assessment of farmer groups on the implementation of the function of agricultural instructors in the village of Tatengesan Satu, Pusomaen Sub-district, Southeast Minahasa Regency. This research was conducted from June to August 2019. The data used are primary data and secondary data. Primary data obtained by interview, based on questionaire, to two farmer groups, each chairman, secretary, treasurer and one member and one agricultural instructor. So that the total respondents were 9 people. Secondary data was obtained from relevant agencies namely through the Agricultural Extension Office (BPP), the Head of Village Office and the Pusomaen Sub-district Office of Southeast Minahasa Regency. Secondary data was also obtained through books obtained from local bookstores and the internet. From internet through google scholar in the form of books, journal articles and theses related to this research topic namely Assessment of Farmer Groups on the Implementation Function of Agriculture Extension. The results showed that the assessment of farmer groups on the implementation of the function of agricultural instructors is not yet fully functioning, where the new agricultural instructors carry out their functions as initiators, facilitators and motivators. While the function of extension workers as a liaison, analyzer and agent of change has not yet been fully felt by the farmer groups. But on the other hand, according to the agricultural instructor, it has been carrying out its functions to the maximum, it's just that the function as an agent of change cannot be fully carried out. This is because extension agents feel that farmers are able to make changes to advance their own farming business to make it more profitable.*eprm*